Comparative study on different peanut digging blades - Omer, Elnougomi A. Gadir; Ahmad, Desa (Universiti Putra Malaysia, 1999)
The performance of four types of peanut digging blades namely; flat-type, curved type, V-shaped type and double discs were evaluated. The results showed that there was a difference in the degree of soil disturbed by the diggers. The percentage of soil disturbed decreased according to the shape of diggers used, namely V-shaped, flat, curved and double discs respectively. The results showed that V-shaped type had lower average draft force for increasing digging depths at both inclined angles of 0 and 40 compared to other digger types. For design of simplicity the V-shaped digger type was the best, and should be used as a digging blade in peanut harvesting machine.